A Study of Vernacular Typhography on Traditional Snack Vendors in Monju Sunday Market Bandung - Dhika Mega Pratama; Kankan Kasmana (Universitas Komputer Indonesia, 2021)
Culinary in Indonesia is diverse and has its own characteristics according to the region of origin. One type of traditional culinary in the city of Bandung is a snack that is easily found and well known, namely Cimol. One of the places where Cimol traders sell their products is Pasar Minggu Monju (Monumen Perjuangan). In selling their products, Cimol traders usually use carts equipped with text or writing that is included in vernacular typography. This is quite interesting to study with the main principles of typography because vernacular typography is made manually. This study aims to see whether vernacular typography is in accordance with the principles of typography. the results of this study are the author's opinion regarding the typography on the cilok merchant's cart which apparently still maintains its identity as a street vendor, especially in the city of Bandung.